2015
DOI: 10.4238/2015.january.23.13
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DNA extraction methods for polymerase chain reaction amplification of guanaco (Lama guanicoe) fecal DNA samples

Abstract: ABSTRACT. Feces-based population genetic studies have become increasingly popular. However, polymerase chain reaction (PCR) amplification rates from fecal material vary depending on the species, populations, loci, and extraction protocols. Here, we assessed the PCR amplification success of three microsatellite markers and a segment of the mitochondrial control region of DNA extracted from field-collected feces of guanaco (Lama guanicoe) using two protocols -Qiagen DNA Stool Kit and 2 cetyltrimethylammonium bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…These results indicate that the use of fresh fecal samples can enhance the success of studies using fecal DNA samples ( Oliveira and Duarte, 2013 ). In contrast, based on samples collected in northern Chile during the summer, Espinosa et al (2015) concluded that fresh feces (based on the presence of mucus or deer observed defecating) and non-fresh feces (no mucus, deer not observed defecating) were equally efficient for successful DNA amplification in ungulate species.…”
Section: Discussionmentioning
confidence: 96%
“…These results indicate that the use of fresh fecal samples can enhance the success of studies using fecal DNA samples ( Oliveira and Duarte, 2013 ). In contrast, based on samples collected in northern Chile during the summer, Espinosa et al (2015) concluded that fresh feces (based on the presence of mucus or deer observed defecating) and non-fresh feces (no mucus, deer not observed defecating) were equally efficient for successful DNA amplification in ungulate species.…”
Section: Discussionmentioning
confidence: 96%
“…The cause could be expressed in two aspects. Firstly, the abundance of the microbiota in the initial samples might have changed after DNA extraction 11 . This change might be relevant to the efficiency of the lysis buffer and the sensitivity of various microbiota to the lysis buffer from different extraction methods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, with the development of molecular biology technology, fecal DNA is extensively used in genetic biology studies for species identification [1517], individual identification [1820], sex identification [2125], population genetic structure [2628], and genetic diversity evaluation [29]. However, fecal sampling has some problems, such as poor fecal DNA isolation quality and low success rate of PCR amplification [30]. Moreover, no study has performed fecal DNA extraction on invertebrates, especially shellfish.…”
Section: Introductionmentioning
confidence: 99%